Cardiovascular risk and electrocardiographic findings on Jalisco population - Acosta-Mayorquín, Arianna; Cardona-Navarro, Norma Alejandra; Aguilera-Mora, Luisa Fernanda; Raffoul Orozco, Abdel Kerim (Horizonte Sanitario, 2022)
Objective: To determine the prevalence of modifiable cardiovascularrisk factors and abnormal electrocardiographic findings in a Guadalajarapopulation.Materials and methods: An analytical cross-sectional study on apopulation of one region in Guadalajara, Jalisco. Sociodemographicvariables, cardiovascular risk factors, blood pressure andelectrocardiographic diagnosis were analyzed.Results: A total of 660 individuals were evaluated (mean age: 56.02years; 69.1% women). The prevalence of overweight/obesity was 75.3%,sedentary lifestyle was 53%, hypertension was 46.5%, diabetes mellituswas 33.03% and dyslipidemias was 25.9%. As an important finding the48.2% of the individuals had electrocardiographic abnormalities. Themost frequent abnormalities were cardiac hypertrophy (14.2 %); and thecomplete and incomplete bundle branch blocks (11.5%).Conclusion: Modifiable cardiovascular risk factors have a higherprevalence than expected. A high prevalence of visible cardiopathieshas been registered by electrocardiogram, this diagnostic test representsa basic tool for the care of the general population.Keywords: Risk factors; Cardiovascular Diseases, Hypertension;Electrocardiography